2012
DOI: 10.1016/j.vaccine.2012.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of vaccination programme of 7-valent pneumococcal conjugate vaccine to the birth cohort in Japan

Abstract: Aiming to introduce 7-valent pneumococcal conjugate vaccine (PVC-7) into routine vaccination schedule, the government of Japan gives a temporary budget to encourage municipalities in launching public vaccination programme which started on November 26, 2010 and ends on March 31, 2012. This study aims to appraise the 'value for money' of PCV-7 vaccination programme from the societal perspective and the budget impact from the perspective of municipalities, which is responsible for providing routine vaccination. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…Our VUR utility results were similar to others for childhood conditions collected via standard interviews (e.g. otitis media 0.9950, bacteremia 0.9921), lending credence to the hypothesis that online TTO determination is a viable mode of utility elicitation [15]. …”
Section: Discussionsupporting
confidence: 79%
“…Our VUR utility results were similar to others for childhood conditions collected via standard interviews (e.g. otitis media 0.9950, bacteremia 0.9921), lending credence to the hypothesis that online TTO determination is a viable mode of utility elicitation [15]. …”
Section: Discussionsupporting
confidence: 79%
“…When evaluated from the societal perspective, it is projected that parental work loss associated with RGE episodes would also be substantially reduced by universal vaccination. The ICER values generated in this analysis are well within the range of other recently adopted childhood vaccines in Japan 70 . Exclusion of parental disutilities is likely to under-estimate the impact of rotavirus and decrease the estimated value of a vaccination program.…”
Section: Discussionsupporting
confidence: 63%
“…In Japan, a study showed that PCV, an on the list of routine immunisation, was found to have <7,400,000 (US$69,811) per QALY gained. 27 If ICERs of rotavirus vaccination estimated in our study were to be compared with that of PCV's, ICERs of rotavirus immunisation program can still be considered as acceptable.…”
Section: Discussionmentioning
confidence: 87%